OUTPATIENT REGISTRY OF CARDIOVASCULAR DISEASES (RECVASA): PROSPECTIVE FOLLOW-UP DATA, ESTIMATION OF RISKS AND OUTCOMES IN PATIENTS WITH ATRIAL FIBRILLATION - M. M. Loukianov; S. A. Boytsov; S. S. Yakushin; S. Yu. Martsevich; A. N. Vorobyev; A. V. Zagrebelnyy; M. S. Kharlap; K. G. Pereverzeva; E. A. Pravkina; S. E. Serdyuk; A. D. Deev; E. N. Kudryashov (Столичная издательская компания, 2015)
Aim. To evaluate outcomes and risk of their occurrence in patients with atrial fibrillation (AF) within 12 months of follow-up in actual outpatient practice. Material and methods. A total of 3690 patients with AF, arterial hypertension (HT), ischemic heart disease (IHD) and chronic heart failure (CHF) consulted by general practitioners and cardiologists of three outpatient clinics of Ryazan, were enrolled into the outpatient REgistry of CardioVAScular diseAses (RECVASA). 530 of 3690 (14.4%) patients had the diagnosis of "atrial fibrillation" in their outpatient charts. Estimation of the end points within 12 months after inclusion into the registry was performed based on the data received from the contacts with patients or a documented fact of death. Results. 39 (7.4%) patients had died during this period [30 (76.9%) of them due to cardiovascular causes], 18 (3.4%) - had undergone stroke, 3 (0.6%) - myocardial infarction, 2 (0.4%) patients had cardiovascular surgery. There were 63 hospitalizations due to cardiovascular diseases (CVD). AF did not lead to significant increase in cardiovascular death risk [odds ratio (OR)=1.31, p=0.21] and stroke risk (OR=1.64, р=0.09) within 12 months after inclusion into the registry, but the risk of hospitalization due to CVD was significantly higher(OR=2.88, р=0.0001). Permanent AF significantly increased the risk of stroke (OR=2.07, р=0.04). Such factors as diabetes, prior stroke, systolic blood pressure (SBP)<110 mm Hg and heart rate (HR)≥90 bpm significantly increased all-cause death risk (OR=2.49, р=0.008; OR=2.46, р=0.01; OR=7.6, р=0.003; OR=15.3, р=0.01, respectively). Patients treated with ACE inhibitors or angiotensin receptor blockers (ARB) had lower all-cause and cardiovascular death risks: OR=0.38, р=0.01 and OR=0.25, р=0.02, respectively. Other drugs revealed no significant influence on prognosis. Conclusion. According to the outpatient registry RECVASA data such factors as permanent type of AF, diabetes mellitus, prior stroke, SBP<110 mm Hg and HR≥90 bpm, ACE inhibitors/ARB prescription significantly influenced prognosis in patients with AF. Estimating outcomes in AF patients, combination with HT, IHD, CHF and non-cardiac comorbidities must be taken into account as well as peculiarities of these diseases drug treatment.